2020
DOI: 10.1136/bmjopen-2019-034143
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of aggression against Spanish nursing personnel and effects on somatisation of physical symptoms

Abstract: IntroductionViolence against nursing personnel in their place of work is a severe problem generating important consequences for these workers. Even though there is a large body of research on the subject, the emotional impact of aggression against healthcare workers continues to be debated.ObjectivesThe objective of this quantitative, observational cross-sectional study was to analyse the effects of aggression against nursing personnel and the mediating role of anxiety in somaticising physical symptoms.MethodT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Thus, our study provides results on this rather unexplored topic, which needs further research. Our findings on the occupational characteristics of HCW throughout the study period revealed that workers younger than 30 years had a significantly higher rate of WPA, likely because they have a shorter length of service and less training; this finding is consistent with other publications mentioning older age as a protective factor against the likelihood of experiencing WPA during the pandemic ( 18 , 23 ). In addition, the incidence among nurses and aides was significantly higher than that among other professional categories (among female nurses and aides, the incidence was higher but not statistically significant), which is consistent with the scientific literature ( 27 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, our study provides results on this rather unexplored topic, which needs further research. Our findings on the occupational characteristics of HCW throughout the study period revealed that workers younger than 30 years had a significantly higher rate of WPA, likely because they have a shorter length of service and less training; this finding is consistent with other publications mentioning older age as a protective factor against the likelihood of experiencing WPA during the pandemic ( 18 , 23 ). In addition, the incidence among nurses and aides was significantly higher than that among other professional categories (among female nurses and aides, the incidence was higher but not statistically significant), which is consistent with the scientific literature ( 27 ).…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to the reported incidence (5.7%) of a cross-sectional study among Italian HCWs during the first year of the pandemic ( 22 ) but are significantly lower than those reported by other studies. For instance, a study in Spain showed that 10% of nurses experienced WPA ( 23 ); a study based on an Italian HCW cohort found a 12-month incidence of new WPA of around 24% ( 24 ); and a meta-analysis conducted in 2019 ( 8 ) found a 12-month prevalence of WPA among HCW of 48.1% in Europe. These differences may be partly explained by the considerable variability in the definitions of aggression, the procedure for recording aggression, and the questionnaires used in the various literature studies, which all hamper comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses also act as counselors to help victims of violence in reducing the impact of trauma experienced as a result of violence. In addition, nurses also play a role in empowering society by forming peer-support groups and as facilitators whose function is to prevent violence against children [21].…”
Section: Introductionmentioning
confidence: 99%
“…Other physical responses, including sleep disturbances, gastrointestinal problems and headaches, can also result from verbal abuse (del Carmen Pérez-Fuentes et al, 2020). Additionally, verbal abuse has been linked to negative organisational outcomes including loss of staff productivity, reduced morale, absenteeism and increased employee turnover intention (Anjum, Ming, Siddiqi, & Rasool, 2018;Lamothe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%